2020
DOI: 10.1523/jneurosci.1370-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Stimulation Improves Postictal Cortical Arousal and Behavior

Abstract: The postictal state following seizures is characterized by impaired consciousness and has a major negative impact on individuals with epilepsy. Previous work in disorders of consciousness including the postictal state suggests that bilateral deep brain stimulation (DBS) of the thalamic intralaminar central lateral nucleus (CL) may improve level of arousal. We tested the effects of postictal thalamic CL DBS in a rat model of secondarily generalized seizures elicited by electrical hippocampal stimulation. Thalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Subcortical disruption may be important causally for the aberrant cortical oscillations we have associated with behavioral impairment 4 . Multiple pathologies and animal model studies have suggested the importance of the intralaminar thalamic nuclei 16,49,50 ; therefore, subcortical targeting of this circuit to improve behavior in a physiologically relevant way may have significant clinical implications 26,28,29,51 (see also https://braininitiative.nih.gov/funded-awards/thalamic-stimulation-prevent-impaired-consciousness-epilepsy). New therapeutic strategies to improve level of consciousness in epilepsy and traumatic brain injury have emerged 52,53 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subcortical disruption may be important causally for the aberrant cortical oscillations we have associated with behavioral impairment 4 . Multiple pathologies and animal model studies have suggested the importance of the intralaminar thalamic nuclei 16,49,50 ; therefore, subcortical targeting of this circuit to improve behavior in a physiologically relevant way may have significant clinical implications 26,28,29,51 (see also https://braininitiative.nih.gov/funded-awards/thalamic-stimulation-prevent-impaired-consciousness-epilepsy). New therapeutic strategies to improve level of consciousness in epilepsy and traumatic brain injury have emerged 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Once training was completed, electrophysiological recordings were performed in the shielded behavioral chambers (Figure 1B), as previously described 28 . Animals were connected from the head‐mounted pedestals to a commutator (Plastics One), headstages (×10 gain), and amplifiers (A‐M Systems, Model 1800, ×1000 gain), and local field potential (LFP) recordings were obtained at 1–500 Hz, with 60‐Hz notch filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al, set out to test this in freely behaving female rats following focal limbic seizures with secondary generalization induced by hippocampal stimulation. 9 …”
Section: Commentarymentioning
confidence: 99%
“…Due to a broader availability of genetic and molecular tools and the ease to manipulate mice in an awake head-fixed condition, we developed an awake, behaving head-fixed mouse model of TLE to measure electrophysiological and behavioral effects of focal limbic seizure. This mouse model will provide new opportunities to identify neuronal mechanisms crucial for maintaining consciousness during focal limbic seizures and explore the possibility to restore cortical function and behavior (Gummadavelli et al 2015; Furman et al 2015; Kundishora et al 2017; Xu et al 2020), providing hope for new treatment approaches to restore arousal in human epilepsy. This novel animal model of focal limbic seizures has been described recently by our group in abstract form and is presented here in greater detail (Sieu et al 2020; Sieu et al 2018; Sieu et al 2019).…”
Section: Introductionmentioning
confidence: 99%